A PORTRAYAL OF NIGERIAN AFTER CIVIL WAR IN CHINUA ACHEBE’S CIVIL PEACE (1971) - Astuti, Anjar Dwi (Fakultas Ilmu Budaya, Universitas Mulawarman, 2017)
African literature has strong relation with colonialism, not only because they had ever been colonized but also because of civil war. Civil Peace (1971), a short story written by Chinua Achebe, tells about how Nigerian survive and have to struggle to live after Nigerian Civil War. It is about the effects of the war on the people, and the “civil peace” that followed. The Nigerian Civil War, also known as the Nigerian-Biafran War, 6 July 1967–15 January 1970, was a political conflict caused by the attempted annexation of the southeastern provinces of Nigeria as the self-proclaimed Republic of Biafra. The conflict was the result of economic, ethnic, cultural and religious tensions among the various peoples of Nigeria. Knowing the relation between the story and the Nigerian Civil War, it is assured that there is a history depicted in Civil Peace. In this article, the writer portrays the history and the phenomenon of colonization in Nigeria by using new historical and postcolonial criticism approaches.Keywords: history, colonization, civil war